GO–Cu7S4 catalyzed ortho-aminomethylation of phenol derivatives with N, N-dimethylbenzylamines: site-selective oxidative CDC. Issue 54 (21st June 2018) - Gupta, Sonu; Chandna, Nisha; Dubey, Pooja; Singh, Ajai K.; Jain, Nidhi
Abstract : An efficient ortho -selective C–H aminomethylation of phenols and naphthols with N, N -dimethylbenzylamines using a GO–Cu7 S4 nanocatalyst is reported. Abstract : Copper chalcogenide nanoparticles (Cu7 S4 ) supported on graphene oxide (GO) have been synthesized for the first time from Cu2 S, and used as highly efficient heterogeneous catalysts for oxidative ortho -selective C–H aminomethylation of phenols with N, N -dimethylbenzylamines. The NPs (30–80 nm) have been characterized by HRTEM, SEM-EDX, PXRD, FTIR, Raman, ICP-AES and XPS analyses. The NP catalyzed sp 2 –sp 3 cross dehydrogenative coupling (CDC) features a broad substrate scope, excellent functional group tolerance, high yields, use of an inexpensive and reusable copper catalyst, mild conditions, and no need for pre-functionalization of substrates.